SECURITY AND PRIVACY ISSUES IN MOBILE NETWORKS, DIFFICULTIES AND SOLUTIONS - Eltahawy, Bahaa (My University, 2014)
Mobile communication is playing a vital role in the daily life for the last two decades; in turn its fields gained the research attention, which led to the introduction of new technologies, services and applications. These new added facilities aimed to ease the connectivity and reachability; on the other hand, many security and privacy concerns were not taken into consideration. This opened the door for the malicious activities to threaten the deployed systems and caused vulnerabilities for users, translated in the loss of valuable data and major privacy invasions. Recently, many attempts have been carried out to handle these concerns, such as improving systems’ security and implementing different privacy enhancing mechanisms. This research addresses these problems and provides a mean to preserve privacy in particular. In this research, a detailed description and analysis of the current security and privacy situation in the deployed systems is given. As a result, the existing shortages within these systems are pointed out, to be mitigated in development. Finally a privacy preserving prototype model is proposed. This research has been conducted as an extensive literature review about the most relevant references and researches in the field, using the descriptive and evaluative research methodologies. The main security models, parameters, modules and protocols are presented, also a detailed description of privacy and its related arguments, dimensions and factors is given. The findings include that mobile networks’ security along with users are vulnerable due to the weaknesses of the key exchange procedures, the difficulties that face possession, repudiation, standardization, compatibility drawbacks and lack of configurability. It also includes the need to implement new mechanisms to protect security and preserve privacy, which include public key cryptography, HIP servers, IPSec, TLS, NAT and DTLS-SRTP. Last but not least, it shows that privacy is not absolute and it has many conflicts, also privacy requires sophisticated systems, which increase the load and cost of the system.
Keywords: Privacy; Anonymity; End to end encryption; IPSec; DTLS-SRTP.; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; fi=Master's Degree Programme in Telecommunication Engineering|en=Master's Degree Programme in Telecommunication Engineering|